Finnish Journal for Romanian Studies 1 - (:unkn) unknown (fi=Turun yliopisto|en=University of Turku|, 2015)
Challenging Identities Robert J. Belton (University of British Columbia, Canada) The Art of Sorel Etrog and His Romanian Background Riikka Niemelä (University of Turku, Finland) Power and Beauty in Salla Tykkä’s ‘Giant’ Diarmuid Johnson (The Academy of Modern Celtic Ethnography, Wales, UK) Mystery and Space. Translating the Poetry of Lucian Blaga Ovidiu Ivancu (Comrat State University, Republic of Moldova) The Romanian Public Discourse on Trans-Forming / De-Forming / Re-Forming / Con-Forming (to) Europe Saila Heinikoski (University of Turku, Finland) European Identity Challenged. Romanian Politicians Discussing Free Movement from the Perspective of Kinship-based Morality Andra Bruciu-Cozlean (University of Tampere, Finland) Romanian Complexes and Identity Crises Book Reviews Anca Sarau-Vuorinen (University of Turku, Finland) Romanian New Wave Cinema. An Introduction (Doru Pop, 2014) Emilia Ivancu (‘Adam Mickiewicz’ University of Poznan, Poland) For a New Theory on Space and Place. A Review of Przestrzeń i miejsce we współczesnych teoriach i praktykach literackich (Space and Place in Contemporary Literary Theories and Practices, Elżbieta Rybicka, 2014)